Factors that affect the properties of magnesium phosphate cement - Li, Yue; Chen, Bing (Construction & building materials, 2013)
•A high content of fly ash up to 60% is incorporated into the magnesium phosphate cement system.•The effects of fly ash on the properties of the MPC system are studied.•The effect of the casting temperature on the setting time of the MPC system is studied.•Hydration products of the MPC system for various curing ages are yielded. Magnesium phosphate cement (MPC) was prepared with dead burned magnesia oxide (MgO), potassium di-hydrogen phosphate (KH2PO4) and some retarders in a given proportion used in the same manner as Portland cement. Factors such as the w/c ratio, casting temperature and fly ash contents that affect the properties of MPC were studied in this paper. The experimental results demonstrate that the setting time was significantly affected by the w/c ratio and casting temperature. Adding fly ash can increase the setting time and flowability of fresh MPC paste. The compressive strengths of MPC paste prepared using various w/c ratios were measured at ages of 3h, 1d, 7d and 28d. The 3-, 7- and 28-day compressive strengths of MPC mortar prepared using various fly ash contents were also measured. The compressive strength of MPC paste decreased with an increasing w/c ratio, and the aged compressive strengths of MPC mortar increased with increasing fly ash content. The results also indicate that adding fly ash can improve the water resistance and dry shrinkage of MPC mortar. Finally, the hydrate products were analyzed using XRD and SEM.